Effect of light restriction on productive results and behavior of broiler chickens - F. Gratta; M. Bošković Cabrol; G. Xiccato; M. Birolo; F. Bordignon; A. Trocino (Poultry Science, 2023)
ABSTRACT: The study aimed to evaluate the effect of light restriction (18L:6D vs. 14L:10D), genotype (A vs. B), and sex on performance, behavior, and meat quality, and the occurrence of wooden breast (WB) and white striping (WS) in broiler chickens. To this purpose 704 one-day-old chickens of 2 genotypes, half males and half females, were reared from hatching until slaughtering at 45 d of age in 32 collective pens (22 chickens per pen). Light restriction reduced growth rate and final live weight (LW), but improved feed conversion ratio (FCR) (P < 0.01) and reduced inactive behaviors of chickens (P < 0.001). Light restriction also reduced WS occurrence in breasts (89.5 to 64.6%; P < 0.001) and reduced meat shear force (2.64 to 2.20 kg/g; P < 0.05) and ether extract content (2.29 to 1.87%; P < 0.05). Regarding genotype, compared to genotype B, chickens of genotype A were heavier (3,242 g vs. 3,124 g; P < 0.01) with higher cold carcass weight and Pectoralis major muscle yield (12.9 vs. 12.0%; P < 0.001) and a higher FCR (1.63 vs. 1.61; P < 0.01). Finally, females had lower final LW (2,852 g vs. 3,513 g) and higher FCR (1.64 vs. 1.59) than males (P < 0.001), but a higher proportion of breast and P. major (P < 0.001), lower cooking losses (P < 0.001) and shear force (P < 0.01), and higher protein content (21.6 vs. 20.7%; P < 0.001). In conclusion, light restriction depressed growth, but was effective in decreasing WS occurrence and improved feed conversion. The decrease in inactive behaviors (sitting/laying) of light-restricted chickens can be positively considered in view of animal welfare.